1972
DOI: 10.1152/ajplegacy.1972.222.5.1161
|View full text |Cite
|
Sign up to set email alerts
|

Digesta flow through the rabbit large intestine

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 0 publications
2
31
0
1
Order By: Relevance
“…This process was accompanied by an increase in motility in the distal colon. These results support the concept that hard faeces are produced by a mechanical separation of liquids and solids during the transport of digesta through the proximal colon (Pickard & Stevens, 1972;Bj6rnhag, 1972Bj6rnhag, , 1981. Our findings also confirm Bj6rnhag's observation (1981 b) that liquid contrast medium was carried from the single haustrated colon towards the caecum during the formation of hard faeces.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This process was accompanied by an increase in motility in the distal colon. These results support the concept that hard faeces are produced by a mechanical separation of liquids and solids during the transport of digesta through the proximal colon (Pickard & Stevens, 1972;Bj6rnhag, 1972Bj6rnhag, , 1981. Our findings also confirm Bj6rnhag's observation (1981 b) that liquid contrast medium was carried from the single haustrated colon towards the caecum during the formation of hard faeces.…”
Section: Discussionsupporting
confidence: 82%
“…Subsequent studies have shown that the formation of dry, hard faeces is not only produced by absorptive processes but also by mechanical separation of liquids and solids during the transit of digesta through the proximal colon (Pickard & Stevens, 1972;Bj6rnhag, 1972Bj6rnhag, , 1981. It has been observed fluotoscopically that contrast medium administered into the rabbit colon was swept back into the caecum by antiperistaltic waves (Pickard & Stevens, 1972;Ijornhag, 1981 b). However, the motor activity ofthe rabbit proximal colon in relation to the passage of digesta is poorly understood and remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The caecal retention time of large particles "CRlp" would correspond to particles larger than 0.3 mm and quickly excreted in hard faeces (BJÖRNHAG, 1972;JILGE, 1982). The caecal retention of fine particles "CRfp" would correspond to particles (<0.3 mm) driven back to caecum by the proximal colon during the period of hard faeces excretion, and which are thus potentially incorporated in caecotrophes and consumed a second time (PICKARD and STEVENS, 1972;BJÖRNHAG, 1981).…”
Section: Rate Of Passage Measurementsmentioning
confidence: 99%
“…Additionally, because of its extending from the opening of the constricted portion to the ileocecal orifice, it is also suggested that the digesta flow from the ileum may turn according to the movement of the valve. Namely, in addition to the digesta flow from the ileum into the cecum, the direct passage of digesta from the ileum into the constricted portion seems to exist, as well as the rabbit [4]. It may flow from the ileocecal orifice to the opening of the constricted portion through the inside space of the elongated valve.…”
Section: Small Intestinementioning
confidence: 99%